The Efficacy of Mirodenafil for Chronic Prostatitis/Chronic Pelvic Pain Syndrome in Middle-Aged Males - Kong, Do Hoon; Yun, Chang Jin; Park, Hyun Jun; Park, Nam Cheol (The world journal of men's health, 2014)
The aim of this study was to investigate the efficacy of mirodenafil in middle-aged male patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). Eighty-eight males with CP/CPPS were randomized to receive either levofloxacin (500 mg/d) (group L, 40 patients) or levofloxacin (500 mg/d) and mirodenafil (50 mg/d) (group ML, 48 patients) for six weeks. The International Prostate Symptom Score (IPSS), National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI), and erectile function (EF) domain scores of the International Index of Erectile Function (IIEF) questionnaire were used to grade symptoms at baseline and 6 weeks after treatment. The mean change in total IPSS from baseline was higher in group ML than that in group L (group L, -1.1 vs. group ML, -4.3; p<0.05). Significant improvements were also seen in the IPSS voiding subscore (group L, -0.7 vs. group ML, -3.0; p<0.05). Changes observed in the NIH-CPSI of group ML at six weeks were greater than those at baseline (group L, -3.2 vs. group ML, -7.2; p<0.05). Significant improvements were seen in the NIH-CPSI voiding (group L, -0.5 vs. group ML, -1.7; p<0.05) and quality of life domains (group L, -1.0 vs. group ML, -1.8; p<0.05). Group ML showed a significantly greater increase in the IIEF-EF score than did group ML (group L, +0.2 vs. group ML, +7.8; p<0.05). Mirodenafil (50 mg once daily) was well tolerated and resulted in significant symptomatic improvement in middle-aged males with CP/CPPS.